MicroRNAs Associated with Parenchymal Hematoma After Endovascular Mechanical Reperfusion for Acute Ischemic Stroke in Rats - Jin-Kun Zhuang; Zhong-Run Huang; Wang Qin; Chang-Luo Li; Qi Li; Chun Xiang; Yong-Hua Tuo; Zhong Liu; Qian-Yu Chen; Zhong-Song Shi (Biomedicines)
Background/Objectives: Hemorrhagic transformation after endovascular thrombectomy predicts poor outcomes in acute ischemic stroke with large-vessel occlusion. The roles of microRNAs (miRNAs) in the pathogenesis of parenchymal hematoma (PH) after endovascular thrombectomy still remain unclear. This study aimed to investigate the miRNA and mRNA regulatory network associated with PH after mechanical reperfusion in an animal stroke model and an oxygen–glucose deprivation/reoxygenation (OGD/R) model. Methods: Twenty-five miRNAs were assessed in a mechanical reperfusion-induced hemorrhage transformation model in rats under hyperglycemic conditions receiving 5 h middle cerebral artery occlusion. The differentially expressed miRNAs associated with PH were assessed in a neuron, astrocyte, microglia, brain microvascular endothelial cell (BMEC), and pericyte model of OGD/R. The predicted target genes of the differentially expressed miRNAs were further assessed in the animal model. The miRNA-mRNA regulatory network of PH was established. Results: Thirteen down-regulated miRNAs (miRNA-29a-5p, miRNA-29c-3p, miRNA-126a-5p, miRNA-132-3p, miRNA-136-3p, miRNA-142-3p, miRNA-153-5p, miRNA-218a-5p, miRNA-219a-2-3p, miRNA-369-5p, miRNA-376a-5p, miRNA-376b-5p, and miRNA-383-5p) and one up-regulated miRNA (miRNA-195-3p) were found in the rat peri-infarct with PH after mechanical reperfusion. Of these 14 PH-related miRNAs, 10 were significantly differentially expressed in at least two of the five neuron, astrocyte, microglia, BMEC, and pericyte models after OGD/R, consistent with the animal stroke model results. Thirty-one predicted hub target genes were significantly differentially expressed in the rat peri-infarct with PH after mechanical reperfusion. Forty-nine miRNA-mRNA regulatory axes of PH were revealed, and they were related to the mechanisms of inflammation, immunity, oxidative stress, and apoptosis. Conclusions: Fourteen miRNAs were associated with PH after mechanical reperfusion in the rat stroke and the OGD/R models. Simultaneously differentially expressed miRNAs and related genes in several cells of the neurovascular unit may serve as valuable targets for PH after endovascular thrombectomy in acute ischemic stroke.